TI_GERICHTE 52.2025.94 vom 13. März 2025 , Commessa pubblica. Valutazione di una referenza come criterio di idoneità - TI Tribunale d'appello (2025)
Commessa pubblica. Valutazione di una referenza come criterio di idoneità